Analisis Komparasi Teknik Rendering Blender Render Dan Cycles Render Pada Video Animasi 3d Tentang Alat Pencernaan Manusia - Nusa Bhakti, Brilian; Nurfaizal, Yusmedi; Anwar, Toni (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2022)
The development of technology from year to year is increasing rapidly. It is undeniable that all aspects of the field have used technology both in the military, education, information and so on. So that the work that usually takes a long time with the development of technology becomes easier and faster. Currently the use of 3D animation is increasingly popular, because it can be applied to various aspects. 3D animation is able to convey even complex concepts that are easy to understand. In addition, 3D animation has the advantage that it makes it easier for the audience to pay attention and focus. Rendering is the process that will determine the result of the 3D animation. The researcher raised the title Comparative Analysis of Blender Rendering Techniques and Render Cycles in 3d Animation Videos About Human Digestive Devices. The parameter used for testing these two techniques is texture. . Meanwhile, when it comes to saving the size of the rendered file, it is better to use Cycles rendering even though the size is not much different. For the quality of rendering, Blender rendering is superior to Cycles rendering. Keyword: 3d animation, Rendering, Cycles render, Blender render